THE ANALYSIS OF FINANCIAL PERFORMANCE FACTORS OF BANK BRI SYARIAT - Budi Subiakto, Tri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Training, Incentive, Supervision, Motivation,  Employee Performance This study aims to analyze the affect factors of BRI Syariah financial performance bank with quantitative approach. In quantitative research which data source secondary, the research method often used is associative causal. The analytical method used is multiple linear regression with SPSS as a statistical tool. The results show that BOPO has a negative and significant effect on ROA. While CAR has a negative but not significant impact on ROA. Then NPF and FDR has positive but not significant effect on ROA. The simultaneous results of CAR, NPF, BOPO, and FDR has significant effect on ROA with a contribution value of 32.8%